The Model of Students’ Emotional Intelligence of Professional Education Program in Indonesia - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Suanto, Elfis; Isnawan, Mohamad Galang (Universitas Muhammadiyah Mataram, 2025)
Recently, there has been a noticeable increase in the significance of students' emotional intelligence (EI) and personality traits regarding self-awareness, self-management, and social awareness. This is to guarantee that their workforce is trained successfully and continuously produces good results. The aims of the study are as follows. (1) to assess how well the proposed model fits the students' data, and (2) to identify the connection between EI domains. The authors opted for a cross-sectional study design by questionnaire survei for EI domains. A total of 1,284 students were involved in this research. The purposive design procedure that resulted in the sample selection involved five departments within the Professional Educational Programs at Universitas Muhammadiyah Purwokerto in Indonesia. The structural model includes all of the interdependencies between the variables. Statistics for Windows 24.0 and Analysing Moment Structures (AMOS) 24 Version were utilized for data analysis. According to the findings, students' levels of self-awareness significantly affect their ability to self-manage in professional education programs, and vice versa. Thus, our study strengthened the idea that EI with an emotion-response process mask is a quality requirement for effective students in any kind of learning environment.